The Figure of the Financier in Dreiser and DeLillo - Grgas-Mufa, Stipe (Array, 2014)
In the article the author compares two literary embodiments of the financier adhereing to the theoretical precepts of new economic criticism. He shows and analyses how the financier in Dreiser and DeLillo are similar and yet how they show differences which can be attributed to the mutations of capitalism.